Determination of Formic Acid and Formaldehyde Formed by Oxidation of Fructose by Potassium Peroxydisulphate - ABUALREISH, M.J.A. (Asian Journal of Chemistry, 2010)
The amounts of formic acid and formaldehyde formed as result of oxidation of a D (–) fructose molecule by potassium peroxydisulphate [S2O82-] were estimated. The values estimated were confirmed by the mechanism of the reaction through analysis of the redox reaction products which revealed the presence of formaldehyde and formic acid.